Production without Empowerment: Work reorganization from the perspective of motor vehicle workers - Lewchuk, Wayne; Robertson, David (Capital & Class, 1997)
This paper examines the relationship between new forms of work organization and worker empowerment from the perspective of workers. The data is drawn from a survey of 5,635 Canadian automobile workers. Workers were asked questions about their work-load, health and safety conditions, empowerment, and relations with management. It examines what it is like to work in plants organized according to the principles of lean production and compares empowerment in lean plants and traditionally organized plants.